2008
DOI: 10.1242/jcs.018648
|View full text |Cite
|
Sign up to set email alerts
|

ROCK-mediated contractility, tight junctions and channels contribute to the conversion of a preapical patch into apical surface during isochoric lumen initiation

Abstract: SummaryROCK-mediated contractility, tight junctions and channels contribute to the conversion of a preapical patch into apical surface during isochoric lumen initiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
124
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(140 citation statements)
references
References 65 publications
15
124
1
Order By: Relevance
“…From 120 minutes to 240 minutes, the lumen volume increased 1.4 times to 8000 μm 3 . In this second phase, our rate of increase is comparable to that seen by Ferrari et al (2008). Although we did not fit such early data points, our model reproduces results comparable to the measurements of Ferrari et al (2008).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…From 120 minutes to 240 minutes, the lumen volume increased 1.4 times to 8000 μm 3 . In this second phase, our rate of increase is comparable to that seen by Ferrari et al (2008). Although we did not fit such early data points, our model reproduces results comparable to the measurements of Ferrari et al (2008).…”
supporting
confidence: 61%
“…Ferrari et al (2008) also measured cyst lumen volumes, focusing on earlier time points. They investigated the development of single MDCK cells into aggregates and found that initially, the lumen volume increases without changes in the total volume or cell number.…”
mentioning
confidence: 99%
“…However, it suggests that Grhl2-deficient collecting duct cells exhibit a defect of lumen expansion that occurs subsequent to adequate cell alignment and polarization. Because previous studies indicated that lumen expansion is driven by fluid accumulation [34][35][36][37] and requires the formation of tight paracellular barriers, 36 we propose that GRHL2 regulates lumen expansion by stabilizing the epithelial barrier via CLDN4 and facilitating apical fluid excretion via RAB25. However, this hypothesis will require additional experimental support.…”
Section: Discussionmentioning
confidence: 87%
“…De novo generation of the apical lumen requires Rab8a-and Rab11a-dependent transport of the apical membrane resident protein podocalyxin/gp135 (PCX; ref. 19) to regions between neighboring cells to initiate lumen formation (10,20).…”
Section: Mutations In Myo5b Independently Affect Localization Of Eithermentioning
confidence: 99%
“…The mCherry-Myo5BΔD overlapped with PCX at the preapical patch (ref. 20; Fig. 3Bb), a luminal domain precursor consisting of a nonexpanded luminal space with closely opposed membranes, but devoid of cell-cell junctions (β-catenin; Fig.…”
Section: Mutations In Myo5b Independently Affect Localization Of Eithermentioning
confidence: 99%